Analisis Proses Perekrutan dan Seleksi Tenaga Pendidik dalam Meningkatan Mutu Pendidikan di MI Shadruddin NW Suralaga - Murni, Abdul Aziz Amir; Sobry, M.; Thohri, Muhammad (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2024)
Educators are a very essential part of educational institutions. MI TGH. Muhammad Shadruddin NW Suralaga faces a shortage of specially qualified educators in implementing education that can support the quality of education. The need to improve the quality of education is carried out by the recruitment process. The purpose of this study is to analyze the recruitment and selection process of educators and assess the quality of education in MI TGH. Muhammad Shadruddin NW Suralaga . The research method used is a qualitative approach with a case study method. Data was collected through in-depth interviews with principals and educators, direct observation, and analysis of related documents. Data analysis was carried out in a qualitative descriptive manner. The results showed that the recruitment of educators was carried out personally without open publication, with the final decision in the hands of the Al Istiqomah Islamic Boarding School Education Foundation NW Suralaga. The selection focuses more on administrative aspects and loyalty to the Nahdlatul Wathan organization, without going through direct tests. Despite the challenge of a shortage of PGSD or PGMI qualified educators, the school is directing teachers to improve their educational qualifications. The quality of education at MI TGH. Muhammad Shadruddin NW Suralaga is demonstrated through B level accreditation, active participation of students in extracurricular activities, and character cultivation through religious activities. Student achievement in academic and non-academic competitions as well as teacher dedication in creating a conducive learning environment contribute to improving the quality of education